Opposite dynamics of GABA and glutamate levels in the occipital cortex during visual processing - Kurcyus, Katarzyna; Annac, Efsun; Hanning, Nina M.; Harris, Ashley D.; Oeltzschner, Georg; Edden, Richard; Riedl, Valentin (Journal of Neuroscience, 2018)
Magnetic resonance spectroscopy (MRS) measures the two most common inhibitory and excitatory neurotransmitters, GABA and glutamate, in the human brain. However, the role of MRS-derived GABA and glutamate signals in relation to system-level neural signaling and behavior is not fully understood. In this study, we investigated levels of GABA and glutamate in the visual cortex of healthy human participants (both genders) in three functional states with increasing visual input. Compared with a baseline state of eyes closed, GABA levels decreased after opening the eyes in darkness and Glx levels remained stable during eyes open but increased with visual stimulation. In relevant states, GABA and Glx correlated with amplitude of fMRI signal fluctuations. Furthermore, visual discriminatory performance correlated with the level of GABA, but not Glx. Our study suggests that differences in brain states can be detected through the contrasting dynamics of GABA and Glx, which has implications in interpreting MRS measurements.
CRIS-Team Scopus Importer:2022-11-28
Keywords: fMRS; GABA; Glutamate; Rs-fMRI; Visual discriminatory performance; Visual system